Early results of treatment for congenital clubfoot using the Ponseti method - Matuszewski, Łukasz (Springer-Verlag, 2011)
The purpose of this study was to evaluate the early results of the Ponseti method in reducing extensive corrective surgery rates for congenital idiopathic clubfoot in patients treated in Children’s Orthopaedic Clinic and Rehabilitation Department Medical University of Lublin between the years 2007–2011. Thirty-five patients with 47 idiopathic clubfeet were followed prospectively while being managed with the Ponseti method. Clubfoot severity was graded with use of the Dimeglio system. The initial correction was achieved, and early results were measured by using Pirani scoring method.